Influences of natural convection on cylindrical objects within a square enclosure with varied shapes - Zakir Hussain; Nusrat ul ain; Naeem Ullah; Zahid Nisar; M.S. Anwar (Case Studies in Thermal Engineering)
Natural convection from varied shapes obstacles inside enclosure has significant role for enhancement of energy efficiency and explored industrial challenges against heat transfer mechanisms. This study presents a comparative analysis for natural convection from cylindrical, octagonal, hexagonal, rhombic and triangular heated objects embedded in a water filled square enclosure. Constant temperature is accounted at vertical walls of enclosure while the horizontal walls are adiabatic. The walls of heated obstacle embedded in enclosure is considered higher temperature than the walls of enclosure. The temperature gradient between walls of enclosure and walls of heated obstacle create deformation in working fluid. A flow model has been developed for considered assumptions against water filled enclosure using conservation principles. The flow model is simplified for Rayleigh number using dimensionless variables. The simplified governing problem is tackled by Finite Element Method. The flow quantities are studied for different values of Rayleigh number. The findings reveal that maximum strength of vorticity is noted in triangular case and minimum strength is observed in hexagonal case. Further, the strength of vorticity enhances against the Rayleigh number. The temperature enhances in upper portion of enclosure when Rayleigh number increase in all cases. Moreover, the isotherm regulates maximum in circular case and minimum in triangular case when compared with other objects. The velocity field for triangular case is noted higher than other obstacles. The heat transfer rate is noted maximum in triangular case and minimum is observed in circular case when compared with other obstacles inside enclosure.